THE POLISH ADAPTATION OF LOCKE’S CSIE QUESTIONNAIRE MEASURING INTER PER SONAL SELF-EFFICACY AND ITS PERSONALITY CORRELATES - Stanisławski, Krzysztof; Strus, Włodzimierz; Cieciuch, Jan (Studia Psychologica: Theoria et praxis, 2017)
The aim of the article is to present the Polish version of Locke’s Circumplex Scales for Interpersonal Efficacy (CSIE) as well as to elucidate the personality correlates of interpersonal circumplex constructs and the scope of the repertoire of interpersonal behaviors. The CSIE is based on Wiggins’ interpersonal circumplex model (Wiggins, Trapnell, & Phillips, 1988) and enables the measurement of the eight facets of interpersonal self-efficacy: Dominant, Dominant & Distant, Distant, Yielding & Distant, Yielding, Yielding & Friendly, Friendly, Dominant & Friendly. The study was conducted on a sample of N = 306. The reliability of one scale (FG – Yielding & Distant) was low, and the reliabilities of the remaining scales were acceptable. The internal structure and construct validity of the instrument were satisfactory. Interpersonal self-efficacy was found to be most strongly associated with the Beta / Plasticity metatrait. This fact was discussed in the context of DeYoung’s (2015) Cybernetic Big Five Theory (CB5 . As indicators of the scope of the interpersonal repertoire two measures were used: interpersonal flexibility (profile elevation) and interpersonal rigidity (vector length). The flexibility of interpersonal self-efficacy and interpersonal traits were associated with extraversion, agreeableness, emotional stability, intellect, Alfa / Stability, Beta / Plasticity, and General Factor of Personality. In turn, the rigidity of interpersonal values and interpersonal traits correlated with extraversion, agreeableness, emotional stability, intellect, Alfa / Stability, Beta / Plasticity, and General Factor of Personality.